Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Motivasi Belajar IPA - suari, ni putu (Jurnal Ilmiah Sekolah Dasar, 2018)
This research aimed at implementing problem based learning model to improve students’ learning motivation in science. The subjects of this classroom action research were 25 students in Grade VI, semester I, academic year 2016/2017 in SD No.1 Darmasaba. Students’ interests were collected using questionnaire and analyzed descriptively. Result showed that after implementing problem based learning model in Cycle I, students’ motivation reached 104.96 which was categorized as highly motivated. Students’ classical completeness was 76%. After Cycle II, students’ motivation reached 121.68 which were categorized as very highly motivated. Students’ classical completeness were 96%. Thus, it is concluded that problem based learning model can be implemented to improve students’ motivation in science